Gottesman-Kitaev-Preskill qubit synthesizer for propagating light - Takase, Kan; Fuku, Kosuke; Kawasaki, Akito; Asavanant, Warit; Endo, Mamoru; Yoshikawa, Jun-ichi; van Loock, Peter; Furusawa, Akira (npj Quantum Information, 2023)
Practical quantum computing requires robust encoding of logical qubits in physical systems to protect fragile quantum information. Currently, the lack of scalability limits the logical encoding in most physical systems, and thus the high scalability of propagating light can be a game changer. However, propagating light also has difficulty in logical encoding due to weak nonlinearity. Here, we propose a synthesizer that encodes Gottesman-Kitaev-Preskill (GKP) qubits in propagating light by exploiting the nonlinearity of photon detectors. This synthesizer is based on an approach what we call Gaussian breeding, leading to the following four advantages: (i) systematic and rigorous synthesis of arbitrary GKP qubits, (ii) use of minimal resources, (iii) high fidelity and high success probability, and (iv) robustness against loss. There has been no protocol that incorporates all these advantages, and thus the proposed synthesizer excels in both performance and feasibility. By employing our method, one can generate GKP qubits using a few to several squeezed light sources, beam splitters and photon detectors.<br
Keywords: Quantum information; Quantum optics